ARTIFICIAL INTELLIGENCE ENABLED INTERNET OF MEDICAL THINGS (IOMT) TECHNIQUES AND METHODS - A. Harb, Hani (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2023)
Artificial Intelligence or AI has been a boon in the medical sector as it allows the overall improvement of medical facilities. The deployment of an efficient and effective management within the healthcare society has been improved with the help of AI. The making of clinical decisions can be enhanced drastically with the aid of AI and its aligning methods. The study would look into the application of AI within the healthcare sector, and observe the pros and the cons of such an integration. The impregnation of the Internet of Medical Things or IoMT within the medical practices would be evaluated and the advantages of disease prediction within the healthcare society would be identified. Such aspects would be beneficial for improving the overall industry of healthcare through effective customer satisfaction. The ethical underpinnings of AI-IoMT are expounded upon, recognizing the imperative of data privacy and security. This exploration delves into encryption mechanisms, blockchain technologies, and patient consent frameworks that ensure patient data remains sacrosanct, fostering trust in this evolving paradigm.